1991
DOI: 10.1039/p29910001941
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of indolic radicals produced upon one-electron oxidation of 5,6-dihydroxyindole and its N(1)-methylated analogue

Abstract: The reactions of indole semiquinone radicals produced following one-electron oxidation of 5,6dihydroxyindole (DHI) and its N-methyl-substituted analogue (MeDHI) have been studied using pulse radiolysis with spectrophotometric detection in the p H range 5-1 0 using different dose/pulse values (1-20 Gy/pulse). Using a dose/pulse of 18.5 Gy the semiquinone radicals of DHI and MeDHl decay predominantly by second order kinetics. The second order rate constants for disappearance of the semiquinone radicals are depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 21 publications
6
25
0
Order By: Relevance
“…Much broader and longer‐lived absorption spectra of the products of disproportionation of the semiquinones of both DHI and DHICA were found here using Br as the initial one‐electron oxidant, than were obtained previously using azide (Al‐Kazwini et al., 1991; Lambert et al., 1989). Although, as noted in the introduction, we cannot yet distinguish between the various quinonoid tautomers as likely products of DHI and DHICA semiquinone decay, the spectrum of the quinonoid species from DHI observed in this study does not appear to correspond with any of the predicted tautomer spectra obtained theoretically by Il'ichev and Simon (2003).…”
Section: Discussionsupporting
confidence: 55%
“…Much broader and longer‐lived absorption spectra of the products of disproportionation of the semiquinones of both DHI and DHICA were found here using Br as the initial one‐electron oxidant, than were obtained previously using azide (Al‐Kazwini et al., 1991; Lambert et al., 1989). Although, as noted in the introduction, we cannot yet distinguish between the various quinonoid tautomers as likely products of DHI and DHICA semiquinone decay, the spectrum of the quinonoid species from DHI observed in this study does not appear to correspond with any of the predicted tautomer spectra obtained theoretically by Il'ichev and Simon (2003).…”
Section: Discussionsupporting
confidence: 55%
“…Indeed we find that at 300 K there should be less than 0.1% SQ. Although we should stress that this calculation is for a single molecule in vacuo it is, of course, in direct contradiction to the evidence [23,24,25,26,27,28] that SQ is one of the building blocks of eumelanin. However, since SQ is widely thought to play an important role in eumelanin, we also consider it here.…”
Section: Resultsmentioning
confidence: 73%
“…However, several pulse radiolysis studies [23,24,25,26,27,28] have indicated the presence of the semiquinone (SQ -also shown in figure 1), a tautomer of IQ, and so we also consider SQ here.…”
Section: Introductionmentioning
confidence: 99%
“…The possible radical intermediates under dis- cussion are shown in Scheme 1. In organic solvents, the protonated form of the semiquinone radicals needs to be considered, which is also dominant in water below pH 5.2 (49,50).…”
Section: Radical Productsmentioning
confidence: 99%